PENGEMBANGAN EKONOMI BENGKULU UTARA MELALUI PENERAPAN AGROMARINE-POLITAN - djawardi, djawardi (Badan Pengkajian dan Penerapan Teknologi, 2009)
North Bengkulu Regency composed of the lowland in the coastal periphery with beautiful coast and the plateau around protected area of Bukit Barisan. The seashore and coastal area unfold as long as region has the big biological resources to be renewed. The mountain ridge area has agricultural produce and forest which the potential to support development of region. Economic analysis of region indicate that economics North Bengkulu District increasing from 4,82 becoming 5,55 percent per year. Manufacturing industries sector, mining and Quarrying sector, Trade; hotel, and restaurant sector, Agricultural sector, Electricity, gas and water supply sector; and also Transportation and communications sector grow up more than 5 percent. AGROMARINE-POLITAN Concept is one of approach to be reference of the regional economic expansion in North Bengkulu Regency. The Implementation of Agromarine-politan required the policy support and strategy development from various sector. There are tourism, agriculture, fishery, transportation, forestry, environmental, manpower and transmigration